IDDF2019-ABS-0027 Urinary formate and glycine are associated with treatment response in patients treated with antibiotics for pouchitis. (June 2019) - Segal, Jonathan; Sarafian, Magali; Jose Serrano Contreras, Ivan; Pechlivanis, Alexandros; Brignardello, Jerusa; Siaw, Yih-harn; Braz, Lucia; Clark, Susan; Holmes, Elaine
Abstract : Background: Restorative proctocolectomy (RPC) is considered the preferred surgical choice for patient with ulcerative colitis (UC) who have failed medical therapy and in some patients with familial adenomatous polyposis (FAP). It has been shown through metabolic profiling of urine that CD patients have higher levels of formate and lower levels of hippurate and 4-cresol sulfate when compared to healthy controls. To date, extensive metabolic profiling in RPC has yet to be studied. This study aimed to determine compounds found in urine that are associated with treatment response in patients that have been treated for pouchitis Methods: Patients with pouchitis were recruited from a single centre. Pouchitis was defined using the pouch disease activity index (PDAI) and pouchitis was considered when the score was ³7. Response to antibiotics was defined as either a 2 points reduction in PDAI. Mid-stream morning urine samples were collected. Samples we stored at -80°C until analysis. 1 H-NMR profile was recorded using the Bruker® Avance III 600 MHz spectrometer, with a Samplejet 96 well autosampler. The full resolution 1 H NMR spectra were imported into the SIMCA-P software package, and multivariate data analyses were carried out. Metabolite assignment was performed by comparing chemical shifts, Jres coupling, and peaks multiplicity with information in databases (such as Human Metabolome DataBase, HMDB). Results: There were 21 patients. The median age of the cohort was 50 years (range 28–79). A total of 11 patients were on antibiotics and 10 patients were off antibiotics. Nine were responders. On multivariate modelling there were significant differences found between responders and non-responders (CV-ANOVA p=0.05) (figure 1 ). Significant spectral differences that corresponded to the multivariate model correlated with Formate (8.84 PPM) Trigonelline (4.45PPM) and Glycine 3.57(PPM) all of which were higher in responders. Conclusions: Trigonelline, formate and glycine may help differentiate patients with pouchitis who will respond to treatments versus those that do not. It is currently unclear as to the mechanism as to why these metabolites are reduced in non-responders and further work is required to understand this and validate our findings.